A Galerkin method of O(h2) for singular boundary value problems - G. K. Beg (International Journal of Mathematics and Mathematical Sciences, 2002)
We describe a Galerkin method with special basis functions for a class of singular two-point boundary value problems. The convergence is shown which is of O(h2) for a certain subclass of the problems.